Interaction of Polyhedral Oligomeric Silsesquioxanes (POSS) Modified with a Metallocyano Complex and Their Application Use as Sensor for the Detection of Isoniazid - Carmo, Devaney Ribeiro do [UNESP]; Peixoto, Murilo Santos [UNESP]; Felipe, Alexsandro dos Santos [UNESP]; Mastelaro, Valmor Roberto; Franco, Fernanda dos Santos [UNESP] (The Electrochemical Society, 2022)
We prepared herein polyhedral oligomeric silsesquioxanes (POSS) modified with zinc and ferrocyanide to create an electroactive nanohybrid material (SZnH) that was then characterized using spectroscopic techniques like FTIR, XPS, SEM, EDX,TEM and CV. Cyclic voltammograms of the SZnH-modified graphite paste electrode (GPSZn) revealed three redox processes with formal potential (Eo') values of 0.33 (I), 0.78 (II) and 1.01 ± 0.01 (III) V (vs Ag/AgCl). The second redox process (II) indicated high current intensities and were used to identify isoniazid in electroanalytical tests. GPSZn was highly sensitive to isoniazid concentrations, presenting two linear response at concentration ranges from 1.0 × 10-5 to 1.0 × 10-3 mol l-1, with the lowest limit of detection (LOD) of 3.70 × 10-6 mol l-1. The material appears to be an excellent candidate for use in developing and applying electrochemical sensors in the detection of isoniazid.
Keywords: polyhedral oligomeric silsesquioxanes (POSS); Voltammetry, sensor, isoniazid; XPS